Relationship of psychological well-being and quality of life with spiritual health in mothers with mentally disabled children - Elnaz Safar Hamidi; Sepideh Bashirgonbadi; Simin Hosseinian (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Mental impairment of a child can have a negative impact on the health of the mother as his primary caregiver. Spiritual health is one of the dimensions of health that has recently been considered by researchers. The purpose of this study was to investigate the relationship of psychological well-being and quality of life with spiritual health in mothers with mentally disabled children in Rasht city. Method: The method of this study was descriptive and correlational. To conduct this research, 150 mothers of mentally retarded children who were studying at a school in Rasht in the academic year of 2017-1018 were selected by available sampling method. After being briefed, they were included in the research and completed Ryff Psychological Well-being Scale (PWBS), Quality of Life Questionnaire (SF-36), and Spiritual Health Scale (SWB). The data were analyzed using regression analysis. In this research, all the Ethical issues were observed and authors declared no conflicts of interest. Results: The results of this study indicated that there is a positive and significant relationship between psychological well-being and spiritual well-being (r=.76, P<.01). This is also true between dimensions of quality of life and spiritual wellbeing including physical health with health Spirituality (r=.65, P<.01), mental health with spiritual health (r=-.83, P<.01), social relationships with spiritual health (r=.57, P<.01) and environmental health with spiritual health (r=.77, P<.01). Based on the results of regression analysis, the spiritual health of mothers of mentally disabled children based on psychological well-being and dimensions of quality of life was predicted. Conclusion: Spiritual well-being is related to psychological well-being and quality of life. Therefore, rise in the level of spiritual health through education and interventions can enhance the quality of life and psychological well-being of mothers and caregivers of mentally disabled children. For downloading the full-text of this article please click here. Please cite this article as: Safar Hamidi E, Bashirgonbadi S, Hosseinian S. Relationship of psychological well-being and quality of life with spiritual health in mothers with mentally disabled children. J Res Relig Health. 2019; 5(2): 37- 49. doi: https://doi.org/10.22037/jrrh.v5i2.18790.